Pengaruh Reputasi Auditor, Komite Audit Dan Ukuran Perusahaan Terhadap Kualitas Audit Pada Perusahaan Sektor Transportasi Yang Terdaftar Di BEI Tahun 2018-2021 - Sheril Kathleen Clarissa; Remista Simbolon (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
This study examines the influence of impact auditors' reputation, auditory committees and corporate size on the quality audits of the transport companies listed in bei 2018-2021 The method of sampling collecting used is sampling impressive. The empirical results of the study show that the auditors' reputation (x1), the auditors committee (x2), and the corporate size (x3) simultaneously affect the quality auditing (y) and to the value of the study of the f for 0,000 < 0,05 and f count 29,372 > f tabel 2,75 of the company listed on the Indonesia Stock Exchange (IDX) 2018-2021.